Efficiency of Low Cost Adsorbents for the Removal of Arsenic from Water - Pokhrel, Megh Raj; Dhital, Raghu Nath (Tribhuvan University Journal, 2013)
Adsorption is one of the primary processes for removing arsenic from drinking water. This study focuses on developing inexpensive and effective adsorbents to remove arsenic from ground water. Eight different types of adsorbents were prepared. Some of these materials were chemically modified. The efficiency of percentage adsorption of arsenate, As (+III) on different materials were investigated at different pH, contact time and initial concentrations. Out of eight different types of adsorbents, the iron-loaded x ant hated orange waste (Fe-XOW) showed high efficiency for the removal of arsenic. It was found that approximately 83 % of arsenate, As (+III) and 87% of arsenate, As (+V) removal could be achieved at optimum pH of 10 and 4respectively. The significant effect of pH was in the range of 9 to12 for As (+III) and 3 to 5 for As (+V). Time dependency experiments for the arsenite uptake showed that the adsorption rate on Fe-XOW was fast initially for 1 hour, followed by slow attainment of equilibrium at 2.15 hour. Adsorption isotherm test showed that equilibrium adsorption data were better represented by Langmuir model than the Freundlich model and the maximum adsorption (qmax) for As (+III) onto Fe-XOW was found to be 53.47 mg/gm. The concentration of arsenic in water sample was determined by standard silver diethyldithiocarbamate spectrophotometric method (SDDC method).